Increased Degenerative Biomarkers in Females with Patellofemoral Pain: A Cross-Sectional Analysis with 6-Month Progression - Lori A. Bolgla; Tiana V. Curry-McCoy; Maya Giddens; Madelyn Overton; Bryaunna Barrera; Jasmine Crockett; Monte Hunter (Diseases)
Background/Objectives: Patellofemoral pain (PFP) is considered a risk factor for knee osteoarthritis (OA) onset. The purpose of this study was to compare degenerative biomarkers in females with and without PFP and to determine changes in these levels, along with pain and function, over 6 months. Methods: All subjects received a knee x-ray to ensure that none had degenerative changes. Urine and serum were collected and analyzed for C-telopeptide fragments of type II collagen (CTX-II) and C-propeptide II (CP-II); these were then expressed as a cartilage degradation: cartilage synthesis ratio (CTX-II:CP-II). Subjects with PFP rated pain using a 10 cm visual analog scale, and function using the Knee injury and Osteoarthritis Outcome Scores-Patellofemoral (KOOS-PF) questionnaire. Subjects with PFP were tested at baseline and at 6 months. Results: Females with PFP had higher levels of CTX-II:CP-II than controls (p < 0.001) and these remained elevated at 6 months (p = 0.82). Females with PFP reported similar levels of pain (p = 0.30) but higher function at 6 months (p = 0.002). However, the 9.0-point increase in KOOS-PF values did not exceed the minimum important change. Conclusions: Females with PFP but no evident structural changes had more elevated biomarkers than controls. This finding suggests that this cohort may have excessive cartilage turnover which may contribute to knee OA.